Abraham Geiger dan Kajian Al-Qur'an - Lenni Lestari (SUHUF, 2014)
One of the result of orientalist research that influences Muslim scholars's faith today is Al-Qur'an as imitation of Judaism. This statement appears from Abraham Geiger, a Judaism orientalist. This writing tries to explain the historical background of Abraham Geiger. Then, the writer explores about the adopted things by Prophet Muhammad from Judaism in Geiger's view and tries to catch the response and reaction of Islamic scholars about Geiger's research. Keywords: Abraham Geiger, historical-critical, Muhammad, Al-Qur'an, Judaism